Reexamining the Mental Pain–Suicidality Link in Adolescence: The Role of Tolerance for Mental Pain. Issue 4 (20th August 2018) - Becker, Gideon; Orbach, Israel; Mikulincer, Mario; Iohan, Maya; Gilboa‐Schechtman, Eva; Grossman‐Giron, Ariella
Abstract : Objective: In this study, we reexamine the mental pain–suicidality link in adolescence, by focusing on mental pain tolerance as a critical factor in explaining youth suicidal behavior. Method: In a series of three studies, participants completed measures of mental pain (tolerance and intensity), emotional regulation, depression, and suicidality. Study 1 included a nonclinical sample of 183 Israeli adolescents. Study 2 included a nonclinical sample of 139 Israeli adolescents, who completed additional measures of self‐esteem, optimism, mindfulness, meaning in life, positive affectivity, and life satisfaction. Study 3 included suicidal psychiatric inpatients ( N  = 24), nonsuicidal psychiatric inpatients ( N  = 24), and nonclinical adolescents ( N  = 24). Results: In Study 1, mental pain tolerance was significantly associated with depression, suicidality, and emotion‐regulation skills. In Study 2, mental pain tolerance was significantly associated with measures of psychological resources. In Study 3, we found that suicidal psychiatric inpatients reported significantly lower levels of mental pain tolerance than nonsuicidal psychiatric inpatients and nonclinical adolescents. No significant group difference was found in the reported intensity of mental pain. Conclusions: Findings imply that mental pain tolerance may be a better indicator for suicidal behavior during adolescence than reported pain intensity.